Dynamic analysis of global warming impact of the household refrigerator sector in Japan from 1952 to 2030. (1st March 2017) - Xue, Mianqiang; Kojima, Naoya; Zhou, Liang; Machimura, Takashi; Tokai, Akihiro
Abstract: The household refrigerators consume large amounts of energy and emit vast refrigerants which contribute to global warming indirectly and directly. The intervention of energy efficiency standard, aging process, and refrigerants substitution result in the performance of the household refrigerator sector varying with time. The present study analyzed dynamic global warming impact of the household refrigerator sector in Japan from the 1950s to 2030 taking into account both the energy effect and chemical effect. The energy effect modelling integrated energy efficiency improvement over year and energy efficiency deterioration over age. The chemical effect modelling involved substitution of three generations of refrigerants on the basis of the flow and stock model. The results showed that the global warming impact of the household refrigerator sector peaked at 25, 104 kt CO2 eq. in 1990 and then decreased to 6506 kt CO2 eq. in 2030. The energy effect accounted for at least 91% and this ratio would be much higher in the future. Both implementation of minimum energy efficiency programs and substitution of refrigerants reduced the global warming impact significantly. This dynamic analysis could provide a holistic picture of the global warming impact of the household refrigerator sector both retrospectively and prospectively from accessing to the market, through rapid growth, to saturation. Highlights: Dynamic energy consumption and refrigerant emissions were modelled. The energy effect dominated the global warming impact. The total global warming impact was modelled to be 6506 kt CO2 eq. in 2030. The global warming impact in the highest nine prefectures in Japan account for 56%.